Transition: an exploration of student nurse experience in their first practice placement - Melling, S.M. (2011)
Nurse education has altered considerably in the past 30 years. The combined demands of a growing population with diverse health needs and an expansion of career opportunities for those traditionally recruited to nursing have made it increasingly difficult to recruit and retain a viable workforce. At the same time pressure to establish nursing as a profession has influenced how the nursing curriculum has been delivered. Schools of nursing are now established in universities and away from clinical control.